Perlindungan Konsumen Produk Ikan Mentah Di Pasar Arumbai Mardika Ambon Terkait Ketersediaan Fasilitas Sanitasi - Marsye R Leterulu; Merry Tjoanda; Agustina Balik (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: The arumbai market as the largest raw fish sales center in Ambon city, is known to have inadequate availability of sanitation facilities and clean water causing raw fish business actors to use sea water that has been contaminated by domestic waste. Resulting in fish being traded to be unhealthy and fresh.Purposes of the Research: To find out and analyze consumer protection for raw fish products in the Arumbai market regarding sanitation facilities and the responsibilities of business actors and managers in providing hygienic raw fish products.Methods of the Research: The research method used is normative juridical, which is focused on providing explanations that explain a particular category. Approach the problem of the statute approach (statute approach) and the conceptual approach (conceptual approach). The collection of legal materials through primary legal materials is then free from secondary legal materials. The processing and analysis of legal materials is described in a qualitative way with the aim of describing the findings in the field.Results of the Research: The absence of legal protection and certainty for consumers of raw fish in the arumbai market, where fish traders do not guarantee the quality of fish to keep it fresh. However, they freely use polluted water to soak the fish. This is because fish traders do not have awareness of their obligations as business actors. And the Government as an institution that is authorized and responsible to the community does not play an active or irresponsible role in supervising and controlling sanitation and clean water facilities at the Arumbai market. Arumbai market fish traders are not aware of their obligations as business actors. So that their responsibility in providing hygienic raw fish is not fulfilled. Market managers, arumbai business actors do not cooperate with the city government to provide sanitation and clean water facilities.